Genome-wide characterization, phylogenetic and expression analysis of ABCG gene subfamily in cucumber (Cucumis sativus L.) - Yuan, Qi; Zhang, Jing; Zhang, Wanlu; Nie, Jingtao (Frontiers in Plant Science, 2023)
The ABCG is the largest subfamily of the ABC family with extensive functions, and only a few members have been identified in detail. However, more and more studies have shown that the members of this family are very important and are involved in many life processes such as plant development and response to various stresses. Cucumber is an important vegetable crops around the world. The cucumber development is essential for its production and quality. Meanwhile, various stresses have caused serious losses of cucumber. However, the ABCG genes were not well characterized and functioned in cucumber. In this study, the cucumber CsABCG gene family were identified and characterized, and their evolutionary relationship and functions were analyzed. The cis-acting elements and expression analysis showed that they played important role in development and responding to various biotic and abiotic stresses in cucumber. Phylogenetic analysis, sequence alignment and MEME (Multiple Em for Motif Elicitation) analysis indicated that the functions of ABCG proteins in different plants are evolutionarily conserved. Collinear analysis revealed that the ABCG gene family was highly conserved during the evolution. In addition, the potential binding sites of the CsABCG genes targeted by miRNA were predicted. These results will lay a foundation for further research on the function of the CsABCG genes in cucumber.